REPRESENTASI MEDIA TERHADAP KASUS PENCEMARAN NAMA BAIK WAKIL WALI KOTA SURABAYA ANALISIS WACANA KRITIS FAIRCLOUGH - Budiman Yunus; Agus Hamdani (MATAPENA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2025)
This study aims to analyze the representation of Surabaya's Deputy Mayor, Armuji, in the news coverage of four online media platforms: Tempo.co, Detik.com, Kompas.com, and iNewsSurabaya.id, concerning an alleged defamation case reported by Jan Hwa Diana. The study adopts Norman Fairclough’s Critical Discourse Analysis approach, which includes three levels of analysis: textual (micro), discursive practice (meso), and social practice (macro). The findings indicate that each media outlet constructs different discourses in positioning Armuji and the reporter. Tempo.co and Detik.com tend to emphasize the voice of the reporter and appear to side with the alleged victim, while Kompas.com and iNewsSurabaya.id offer more balanced reporting by presenting both perspectives. Word choices, source quotations, and narrative structures are key tools in shaping social realities and ideologies within news discourse. These results affirm that the media serve not only as conveyors of information but also as active agents in shaping meaning and power relations in society. Keywords: Critical Discourse Analysis, Fairclough, Online Media.